SCHEDULING LECTURESOFTWARE USING WEB-BASED FRAMEWORK CODEIGNITER (A CASE STUDY: FACULTY OF SCIENCE AND TECHNOLOGY UIN SUNAN GUNUNG DJATIBANDUNG - Mohamad Irfan; Nur Lukman (JURNAL ISTEK, 2012)
Nowadays, using of the computer has increased widely, the technology used is growing rapidly every field, and technological Information become an important part of it that makes easy and speed in producing the latest information. The private or public agencies now competiting to make and build the information system to help their work. The Faculty of Science and Technology UIN Sunan Gunung Djati Bandung is an institution under theauspices ofthe Ministry ofReligious Affairswhichcannot be separatedas an educational institutionthat requiresasystemthat providesefficient service,fast, and transparent. In this case, Scheduling Lecture Application is one of the information technology used in the Faculty of Science and Technology State Islamic University Sunan Gunung Djati Bandung. Scheduling classes is not an easy task because it must consider many constraints or limitations, the limitation of humans to arrange all the existing constraints make them doing an error work sometimes, this factor is difficult to avoid. Therefore, it takes a scheduling lecture system that can perform calculations and checking an error as facilitation for officers easy in scheduling classes. In this case the writer uses the method of manufacture of the Rational Unified Process (RUP), which is proses of iterative software development that focuses on the use case driven.